1996
DOI: 10.1056/nejm199606203342504
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Wider Use of Surfactant Therapy on Neonatal Mortality among Blacks and Whites

Abstract: After surfactant therapy for RDS became generally available, neonatal mortality improved more for white than for black infants with very low birth weights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 26 publications
2
69
1
Order By: Relevance
“…A study among very low birthweight infants in St. Louis also found that only 56% of all infants with diagnosis of RDS admitted to a NICU were administered surfactants during 1991 to 1992. 21 While the majority of the decline in the male excess in deaths was due to RDS, there was also some decline in prematurity-related deaths. While specific interventions responsible for the decrease in prematurity deaths could not be ascertained from the data, it is likely to reflect improvement in neonatal intensive care for very premature births.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study among very low birthweight infants in St. Louis also found that only 56% of all infants with diagnosis of RDS admitted to a NICU were administered surfactants during 1991 to 1992. 21 While the majority of the decline in the male excess in deaths was due to RDS, there was also some decline in prematurity-related deaths. While specific interventions responsible for the decrease in prematurity deaths could not be ascertained from the data, it is likely to reflect improvement in neonatal intensive care for very premature births.…”
Section: Discussionmentioning
confidence: 99%
“…26 To minimize incorrect recording of closely related disease categories, we combined the causes of death into broader groups. 21 The linked birth and death data also often undercount use of steroids since it may be under-reported on birth certificates. 19 We could not quantify the extent of this undercount if any.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Differences in treatment according to race have been noted in adult diseases such as breast cancer, coronary heart disease, hypertension and schizophrenia. [17][18][19][20] We postulated that differences in delivery patterns for breech presentation may also exist by race, thereby contributing to racial disparities in neonatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…An effective therapy that has differential access according to socioeconomic characteristics or ethnicities may cause a divergence in health status outcomes among segments of the population (54). Although Internet access is skewed toward wealthier, more educated users (55, 56), market forces may shape a substantially more equitable distribution.…”
Section: Inequitable Access To Technologymentioning
confidence: 99%